Parental Support in Psychological Rehabilitation of Child Victims of Sexual Violence: A Qualitative Study - Eka Ayu Syahfitri, Regita; Rokhmah, Dewi; Nafikadini, Iken (Interest : Jurnal Ilmu Kesehatan, 2024)
Background: Sexual violence was the most common, Data from the Regional Technical Services Unit for the Protection of Women and Children (UPTD PPA) of Jember Regency showed that there were 75 cases of sexual violence against children in 2022 and 73 cases of sexual violence against children in 2023. This research aimed to analyse aspects of parental social support in the psychological rehabilitation of child victims of sexual violence in the Jember Regency. Methods: This research was qualitative research with a case study approach.  Data were collected through in-depth interviews with 3 main informants, which are parents of child victims of sexual violence with the age criteria of 7-18 years, 2 additional informants, which are family members or closest people from the victim's parents and 1 key informant, which the Regional Technical Services Unit for the Protection of Women and Children (UPTD PPA) of Jember Regency. Informants of this research are based on the willingness of informants to be interviewed in accordance with an ethical review of the confidentiality of informant information. Results: The results showed that parents had provided emotional support to child victims of sexual violence by reporting to the police; providing affection, instrumental support by fulfilling daily needs, informative support by giving advice to children, and providing appreciation support by accepting the child's condition, providing support to children to undergo rehabilitation so as not to experience prolonged trauma. Conclusion: Providing aspects of parental social support has been given to their children who are victims of sexual violence.